URGENCY OF BREAST FEEDING PROTECTION AND SUPPORT IN THE CHECHEN REPUBLIC AND REPUBLIC OF INGUSHETIA - P.M. Evloeva; L.V. Abolyan ("Paediatrician" Publishers LLC, 2011)
Complex medico-sociological survey included demographic analysis and morbidity among children of first year of life in the Chechen Republic and Republic of Ingushetia (2005-2009), data from interviews with mothers upon popularity and duration of breast feeding, as well as analysis of medico-social factors that affect these parameters. Results of the survey allowed to make a sketch of concrete measures work optimization of medico-prophylactic institutions, that aim at popularity boost of breast feeding.Key words: chechens and ingushs, medico-demographic parameters, morbidity and mortality of children of first year of life, duration and popularity of breast feeding, obstetrical and pediatric medical prophylactic institutions. (Voprosy sovremennoi pediatrii - Current Pediatrics. - 2011; 10 (6): 20-25.)